A targeted and nontargeted metabolomics study on the oral processing of epicatechins from green tea. (1st June 2022) - Cao, Qing-Qing; Fu, Yan-Qing; Liu, Yu-Yi; Qin, Yumei; Chen, Jian-Xin; Yin, Jun-Feng; Xu, Yong-Quan
Highlights: Epicatechins were all significantly lost during OP. Non-galloylated catechins were lost through dimerization and epimerization. Galloylated catechins were lost through hydrolysis, complexation, or dimerization. EGCG was the least stable of the epicatechins, whereas EC the most. EGCG was susceptible to pH condition, mucin, and esterase, in human oral cavity. Abstract: Oral processing (OP), referring to the whole process of food digestion in human mouth, has a major influence on food flavor perception. This study focused on the compositional changes of the four green tea epicatechins (viz., EC, EGC, ECG, EGCG) during OP, based on targeted and nontargeted metabolomics. It was found that the four epicatechins were all extensively lost through transformation undergoing OP, among which EC was the most stable one, whereas EGCG the least. EGCG was further revealed to be susceptible to human oral cavity in the simulated OP in vitro . It could be converted physically by precipitating with mucin in saliva, and chemically through hydrolysis and dimerization, mediated mainly by the neutral pH condition. The OP of epicatechins also caused salivary composition changes possibly involving health benefits of green tea. These findings could raise awareness of the interactions between epicatechins, or any other food materials, with human mouth.